IL1RL1 polymorphisms rs12479210 and rs1420101 are associated with increased lung cancer risk in the Chinese Han population - Li, Qi; Zhang, Chan; Cheng, Yujing; Yang, Xin; Chen, Wanlu; He, Kunhua; Chen, Mingwei (Frontiers in Genetics, 2023)
Background: Lung cancer is one of the most common human malignant diseases. In this study, we aimed to explore the association between IL1RL1 genetic polymorphisms and lung cancer risk in the Chinese Han population. Methods: We selected and genotyped six SNPs in the IL1RL1 gene using the Agena MassARRAY system in 507 lung cancer patients and 507 healthy controls. The association between IL1RL1 variants and lung cancer risk was assessed using logistic regression to calculate odds ratios (ORs) and 95% confidence intervals (CIs). Multi-factor dimensionality reduction (MDR) was used to analyze the impact of SNP-SNP interactions on the risk of lung cancer. Results: The results of overall analysis indicated that rs12479210 (T vs. C: OR = 1.42, FDR-p = 0.002; TC vs. CC: OR = 1.70, FDR-p < 0.0001; TT vs. CC: OR = 1.77, FDR-p = 0.032; TT-TC vs. CC: OR = 1.71, FDR-p = 0.001; additive: OR = 1.44, FDR-p = 0.001) and rs1420101 (T vs. C: OR = 1.31, FDR-p = 0.036; TT-TC vs. CC: OR = 1.42, FDR-p = 0.031; additive: OR = 1.30, FDR-p = 0.030) were associated with an increased the risk of lung cancer among the Chinese Han population. Stratified analysis also found the association between these two SNPs and lung cancer risk. However, there were no significant association observed between the other four SNPs (rs3771180, rs3771175, rs10208293, and rs10197862) in IL1RL1 and lung cancer risk. Furthermore, MDR analysis showed that rs12479210 was the best single model with the highest testing accuracy (0.566) and perfect CVC (10/10) for predicting lung cancer risk. The expression level of the IL1RL1 gene is lower in lung cancer tissue than normal tissue, and there are significant differences in the expression levels of IL1RL1 between rs12479210 and rs1420101 genetypes in lung cancer tissue (p < 0.05). Conclusion: Our findings suggest that IL1RL1 genetic variants (rs12479210 and rs1420101) are associated with an increased lung cancer risk in the Chinese Han population. These risk variants may serve as biomarkers for the prevention and treatment of lung cancer.